How EFL student teachers bolster 4C learning skills in lesson planning - Agung Ginanjar Anjaniputra; Zuhrul Anam (English Language Education Study Program, Teacher Traning and Education Faculty, Universitas Muhammadiyah Cirebon, 2023)
This case study investigates how an EFL teacher educator flipped the classrooms to promote 4C learning skills among student teachers planning a lesson. In lesson planning, collaborative works and participation of students are vital as both help students develop their knowledge. The flipped classroom as a breakthrough in the teaching and learning process provides more personalized learning and interaction from which students can benefit. Its implementation along with the 4C learning skills is required to face the new landscape of education after learning loss of the pandemic as the discrepancy of digital access and learning remains high. Thus, collaboration, communication, creativity, and critical thinking in flipped lesson planning activities are required to be illustrated. The data were collected from observation, interviews and document analysis. The findings suggest that pedagogical knowledge, technological knowledge and content knowledge are must-have competences of today’s educators to meet the demand of the 21st century learners. In addition, lesson planning for the novice is a long, meticulous process that cannot be completed in one go, and is integral to collaborative and communicative tasks to yield a more well-informed and sound outcome while accommodating creativity and critical thinking. Moreover, benchmarking and standardizing teachers, lecturers, or educators should be administered at some levels. Keywords: 4C learning skills; flipped learning; lesson planning; preservice teachers